Supply Chain Risk Evaluation at PT. XYZ Using the House of Risk Method - Fanni, Tio; M.L. Denny Tewu; Tarsicius Sunaryo (JURNAL MANAJEMEN MOTIVASI, 2026)
This study evaluates supply chain management risks at PT. Fantasi Rekasembada using the House of Risk method and ISO 31000 approach. The main problems include unstable raw material supply, delays in imported components, dependence on international suppliers, steel availability fluctuations, and external disruptions. This descriptive study uses semi-quantitative analysis with data collected through observation, interviews, risk questionnaires, and company documentation. The analysis identifies risk events, risk agents, severity, occurrence, correlation, and priority risks. The findings are expected to support systematic risk mitigation, improve supply chain resilience, maintain material availability, control operational costs, and increase customer satisfaction. Keywords: Supply Chain Management; House of Risk; ISO 31000; Risk Management; Supply Chain Risk Management; Risk Mitigation